Symbolic Communication of Tourism Images in Soap Opera Televisions - I Gusti Agung Alit Suryawati (Ikatan Sarjana Komunikasi Indonesia, 2021)
Tourism in Bali is growing so rapidly that it continues to increase every year. The increasing number of foreign and domestic tourist arrivals leads to an increase in domestic services and promotions. Arief Yahya assessed that film had become a useful medium and contributed greatly to promoting Indonesian tourism. The aim of this research is to know how soap opera and film could be used as a means of promotion to know about Tourism in Bali and other state problems: (1) How Broadcasting as a mass communication activity functions as a medium of information, education, entertainment, health, control and social control; (2) How to carry out the function of soap opera and film as a means of promoting Tourism inBali;(3), How broadcasting also has economic and cultural functions. Theory and Method: Symbolic Theory and Method use perception and qualitative analysis which explore by watching the eat, pray, and love films and some soap operas whose shooting take place in Bali. They can serve as a reference for the industrial world to make films that can inspire audiences to come to the place or location of the film, and also a reference for tourists who would come to Bali.